POTENTIAL HOLISTIC PREVENTIVE AND THERAPEUTIC EFFECTS OF GARCINIA MANGOSTANA EXTRACT OR ISOLATES IN TYPE 2 DIABETES MELLITUS: A REVIEW - HANRAHAN, JOANNA ERIN; SUBROTO, PRISCILLA AYA MAHESWARI; PRIAWAN, RAHARDI PRASETIA; KRISNAMURTI, DESAK GEDE BUDI (International Journal of Applied Pharmaceutics, 2019)
Objective: The need for long-term medication in diabetes mellitus has led to a search for herbal medicines as alternative treatments. Several studies have shown that extract or isolates of Garcinia mangostana can help prevent and treat type 2 diabetes mellitus (T2DM). Methods: This review was conducted by searching various databases, including PubMed, ClinicalKey, ScienceDirect, and EBSCOhost. We analyzed papers published within the previous 10 y. Results: All in vitro, in vivo, and clinical studies that evaluated the pharmacological effects of extract or isolates of G. mangostana in T2DM were reviewed. G. mangostana was found to suppress adipogenesis and regulate lipid homeostasis, thus improving lipid profiles and preventing T2DM. G. mangostana also demonstrated hypoglycemic properties, including the ability to decrease fasting blood glucose and mildly increase pancreatic β-cell numbers and activity. The mangosteen-treated group in one study showed a decrease in Homeostatic Model Assesment for Insulin Resistance (HOMA-IR), indicating improved insulin sensitivity, along with a significant decrease in the high-sensitivity CRP (hs-CRP) levels. Histopathology showed that the α-mangostin-treated group had less damage to pancreatic β cells, healthier hepatocytes and central veins, and less glomerular and tubular epithelial necrosis than the diabetic control group. Moreover, the antioxidant effect of G. mangostana was shown to protect against the micro-and macrovascular damage caused by T2DM. Conclusion: Extract or isolates of G. mangostana possess strong potential to prevent and treat T2DM. Further research evaluating long-term outcome biomarkers in humans is needed to confirm the drug’s glycemic control capacity.